2016
DOI: 10.1038/srep25658
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of Endogenous Immunoglobulins by Endothelial Cells at the Blood-Brain Barrier

Abstract: The Blood-Brain Barrier (BBB) restricts access of large molecules to the brain. The low endocytic activity of brain endothelial cells (BECs) is believed to limit delivery of immunoglobulins (IgG) to the brain parenchyma. Here, we report that endogenous mouse IgG are localized within intracellular vesicles at steady state in BECs in vivo. Using high-resolution quantitative microscopy, we found a fraction of endocytosed IgG in lysosomes. We observed that loss of pericytes (key components of the BBB) in pdgf-bret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 31 publications
(57 reference statements)
8
78
0
Order By: Relevance
“…Both uptake and transport of IgGs were altered in disease states, with the most significant increases in uptake and transport occurring with Aβ₁₋₄₂ incubation. The IgGs may be accumulating within the cells but are ultimately recycled back to the luminal compartment (Deane et al, 2005;Schlachetzki et al, 2002;Zhang & Pardridge, 2001) or are degraded within lysosomes (Villaseñor et al, 2016). Transport of IgGs was about twofold higher after incubation with Aβ₁₋₄₂, which is consistent with a study that showed a twofold increase in IgG transport after incubation with Aβ₁₋₄₂ in a primary murine BBB model (Wuest & Lee, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Both uptake and transport of IgGs were altered in disease states, with the most significant increases in uptake and transport occurring with Aβ₁₋₄₂ incubation. The IgGs may be accumulating within the cells but are ultimately recycled back to the luminal compartment (Deane et al, 2005;Schlachetzki et al, 2002;Zhang & Pardridge, 2001) or are degraded within lysosomes (Villaseñor et al, 2016). Transport of IgGs was about twofold higher after incubation with Aβ₁₋₄₂, which is consistent with a study that showed a twofold increase in IgG transport after incubation with Aβ₁₋₄₂ in a primary murine BBB model (Wuest & Lee, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…A recent study (Villaseñor et al . ) implicated Rab17‐dependent sorting microtubules in directing monovalent TfR antibody toward successful transcytosis; the bivalent TfR antibody‐TfR clusters were excluded from sorting microtubules by slower diffusion and were targeted for degradation. This hypothesis did not take into account the presence of various forms of the TfR on the surface of cells, some of which are naturally dimerized; nor was a range of affinities tested in a monovalent format.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, (Villaseñor et al . ) they showed a preferential sorting of a monovalent TfR antibody into sorting tubules which facilitated transcytosis across the BBB. However, a bivalent antibody that bound TfR in a pH‐sensitive fashion with lower affinity at acidic pH, typical of endosomal compartments, was found to escape degradation and release more efficiently on abluminal side of the BBB model in vitro (Sade et al .…”
mentioning
confidence: 94%
“…Whereas the molecular mechanisms of endocytosis and recycling triggered by specific receptor-ligand interactions, notably transferrin binding to TfR, have been studied extensively in various cell types, 42,46 the intracellular sorting of antibodies that leads to their polarized transport and transcytosis across brain endothelium is less well understood. 47 Some specific pathways favoring transcytosis have started to emerge from this study; in particular, it appears that a subset of MVBs bearing markers of exocytosing MVBs may be an important pathway leading to abluminal exocytosis of the BBB-crossing FC5 antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, A20.1Fc showed slightly higher P app values in vitro and measurable CSF levels in vivo compared to A20.1, suggesting that Fc fragment may contribute to low, but detectable non-specific penetration of antibodies into the brain described in several studies. 5,6,13 A recent study 42 using high-resolution quantitative microscopy showed that lysosomal degradation of low levels of IgGs internalized into BEC from systemic circulations may be further limiting the antibody access to the brain.…”
Section: Discussionmentioning
confidence: 99%